2018
DOI: 10.4194/1303-2712-v18_2_07
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Trophic ecology of eight species of nemipterid fish including Nemipterus mesoprion, N. hexodon, N. nemurus, N. nematophorus, N. tambuloides, N. peronii, N. furcosus and Scolopsis taeniopterus were studied to investigate their diet composition and trophic relationships between them. Our findings revealed that they were specific predators feeding mainly on shrimp and fish. N. nemurus and N. tambuloides were the most piscivorous species of them all, and N. mesoprion was a specific shrimp predator. In general, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Studies on trophic relationships have shown that many species, including cephalopods change feeding habits with increasing size or during maturation to maximize energy intake, enhance growth rate and minimize the risk of predation [55][56][57][58][59][60] . In the present study, however, the female D. gigas appear to prey on similar prey items before and after maturation because no significant differences were found in the relative abundance of each fatty acid among maturity stages for the ovary, mantle muscle (except 20:5n3) and digestive gland (Supplementary Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on trophic relationships have shown that many species, including cephalopods change feeding habits with increasing size or during maturation to maximize energy intake, enhance growth rate and minimize the risk of predation [55][56][57][58][59][60] . In the present study, however, the female D. gigas appear to prey on similar prey items before and after maturation because no significant differences were found in the relative abundance of each fatty acid among maturity stages for the ovary, mantle muscle (except 20:5n3) and digestive gland (Supplementary Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most of the literature on trophic interactions, especially in the Mediterranean, usually focuses on the diet comparison of just two or three species (Valls et al 2011(Valls et al , 2017Barría et al 2015Barría et al , 2018. More complex studies are limited to a few papers, published in recent decades and focusing on the main predator groups, like bony fishes (Cabral et al 2002;Valls et al 2014b;Karachle 2017;Park et al 2017;Paul et al 2018), elasmobranchs (Orlov 1998;Valls et al 2011; Barría et al 2015Barría et al , 2018Kousteni et al 2018), cetaceans (Liu et al 2015) and cephalopods (Cherel et al 2009), while studies on betweentaxa interactions are even fewer (Valls et al 2014a(Valls et al , 2017. Concentration on large predator groups is driven by the predators roles in the food chain, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Islam et al [26] also reported that U. chinensis and U. duvaucelii in the southwest of the Gulf of Thailand of different size-classes had high overlap in their food items and minimal dietary shift with ontogeny. Preying on the common prey items with increasing size may be an optimal foraging strategy for squid to maximize energy intake, enhance their growth rate and minimize predation risk [80,81]. We also found non-significant effects of sampling station on the fatty acid composition for either species and among the four squids considered simultaneously.…”
Section: Plos Onementioning
confidence: 64%
“…It is known that overlap in dietary resources between sympatric species may lead to spatial segregation, which appears to be the essential for coexistence [2,73,81]. The four squids exhibit the characteristics of demersal predators, evidenced by the non-significant differences and high levels in the relative content of 16:0, 20:5n3 and 20:4n6, which are indicators for demersal habitat [76,78].…”
Section: Plos Onementioning
confidence: 99%